NEGÓCIOS DO REINO LUSITANO NO ALÉM-MAR: agentes mercantis no Maranhão (1706-1750) - LOPES, Ana Paula Durans (2021)
This work deals with the commercial exchanges performed out by commercial agents and the networks of sociabilities formed in the context of insertion in the complex dynamics of the portuguese administration overseas in the first half of the 18th century. The research deals with thinking about the connections formed between subjects and regions, considering essential elements, such as the main commercial activities in the captaincy of Maranhão and the role of overseas authorities in the State's business in the face of the circulation of “earth money”. For the State of Maranhão, monetization was not officially applied until 1748, the year of the Royal Decree of authorization, at this juncture for the State of Maranhão and Grão-Pará, commercial transactions occurred when paying for natural products. The analysis of the business of the Portuguese kingdom in the captaincy of Maranhão interconnects the sources of the Overseas Council and municipal assembly, the use of different sources provides a more detailed look at the presence of overseas businesses, as it shows the presence of authorities, businessmen and involvement from other social strata.